Due domande sulla natura dell’immaginazione - Spinicci, Paolo (Bollettino Filosofico, 2018)
The aim of this paper is to focus on a particular subject – imagination – in order to set limits and to underscore the validity of a phenomenological understanding of our experience. Imagination is, first of all, a general heading under which we comprehend a range of psychological faculties, whose adaptive meaning (still poorly understood) deserve to be analyzed from a naturalistic point of view. Under the same heading we are used to understand a variety of social and individual activities, of playful gestures and utterances, which belong to the realm of meaning and which deserve to be analyzed and clarified from a descriptive point of view. Phenomenology, as a description of the meaning of our personal experience, has here its possible field of application.